IbM Pelatihan Effective Communication Skill Bagi Pengelola Usaha Objek Wisata Tiga Ras Kabupaten Simalungun - Anggia Sari Lubis; Ratna Sari Dewi; Ananda Anugrah Nasution; Semangat Juang Lahagu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Effective communication skills training for managers of the Tiga Ras tourism object in Simalungun Regency as a form of soft skills development in order to further increase professionalism in organizational business, because the tourism sector will be interact with many people. Following by business managers at the Tiga Ras tourist attraction in Simalungun Regency. The result of this Community Service is effective communication skills training which is very useful in improving self-quality, developing effective communication skills to support the sustainable of business. The location of this service is a tourist attraction for the Tiga Ras of Simalungun Regency. The method is lectures and practices